The catalytic mechanism of Escherichia coli endonuclease VIII: Roles of the intercalation loop and the zinc finger - Kropachev, Konstantin Y. (2006)
Endonuclease VIII (Nei) excises oxidatively damaged pyrimidines from DNA and shares structural and functional homology with formamidopyrimidine-DNA glycosylase. Although the structure of Escherichia coli Nei is solved, the functions of many of its amino acid residues involved in catalysis and substrate specificity are not known. We constructed a series of Nei mutants that interfere with eversion of the damaged base from the helix (QLY69-71AAA, ΔQLY69-71) or perturb the conserved zinc finger (R171A, Q261A). Steady-state kinetics were measured with these mutant enzymes using substrates containing 5,6-dihydrouracil, two enantiomers of thymine glycol, 8-oxo-7,8-dihydroguanine and an abasic site positioned opposite each of the four canonical DNA bases. To some extent, all Nei mutants were deficient in processing damaged DNA, with mutations in zinc finger mutants generally having a more profound effect. Wild-type Nei showed prominent opposite-base specificity (G>C≈T>A) when the lesion was 5,6-dihydrouracil or cis-(5S,6R)-thymine glycol but not for other lesions tested. Mutations in the Q69-Y71 loop eliminated this effect. Only wild-type Nei and Nei-Q261A mutants could be reductively cross-linked to damaged base-containing DNA. Experiments involving trapping with NaBH(4) and the kinetics of DNA cleavage catalyzed by Nei-Q261A suggested that this mutant was deficient in regenerating free enzyme from the Nei-DNA covalent complex formed during the reaction. We conclude that the opposite-base specificity of Nei is primarily governed by residues in the Q69-Y71 loop and that both this loop and the zinc finger contribute significantly to the substrate specificity of Nei.